The dynamics of domestic revenue mobilization across four decades - Annalena Oppel; Kyle McNabb; Daniel Chachu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
We utilize the recently updated UNU-WIDER Government Revenue Dataset, which covers key indicators on tax and non-tax revenues for 196 countries since the 1980s, to study the dynamics of government revenue tax collection across selected periods from 1985 up to the most recent available year (2019). In doing so, we propose a new approach that highlights the direction, intensity, and continuity of trends in total tax and total revenue collection, with implications for aid, fiscal policy, and sustainable development. We find that in the early to late 2000s, tax- and revenue-to-gross domestic product ratios experienced an upward surge on average; however, this does not uniformly apply to all regions. In addition, for countries that witnessed moderate to high growth rates in total revenues in the early to late 2000s, moderate growth levels may have turned out to be more sustainable. This, as well as explorations of our methodology, poses topics for further investigation to contextualize global patterns, particularly regarding drivers of domestic revenue mobilization improvement or decline.
Keywords: E00; H2; Y10; 330; domestic revenue mobilization; Government Revenue Dataset; tax; sustainable development; aid; fiscal policy